Successful PD-1 inhibitor treatment in a patient with refractory transformed follicular lymphoma who failed to respond to CAR-T cell therapy: a case report and literature review. Issue 10 (2nd December 2021) - Zheng, Weicheng; Xue, Qingfeng; Sha, Xueping; Wang, Yao; Wang, Yuan; Liu, Juan; Zhang, Yaping; Shi, Wenyu
ABSTRACT: Follicular lymphoma (FL) accounts for approximately 35% of all non-Hodgkin lymphomas and can progress to diffuse large B cell lymphoma (DLBCL) at a rate of 2% per year. Here, we present a 56-year-old female patient who was diagnosed with grade 3a FL. Further pathological investigation revealed that the lymphoma had transformed into DLBCL following six courses of R-CHOP regimen, and further disease progression was observed after two courses of R2-GemOx. We ultimately failed to collect hematopoietic stem cells after two courses of R2-ICE. CD-22 CAR-T cell therapy salvaged the patient; however, a new soft tissue mass of 4.8 × 4.1 cm rapidly emerged in the patient's right lung. Following the observation of strong tissue staining of PD-L1 (90%), the patient was administered PD-1 inhibitor and 26 Gy of radiotherapy and has maintained progression-free survival at more than 15 months of follow-up. Transformed FL with strong PD-L1 expression showed a poor response to standard immunochemotherapy. Our findings support the potential benefit of PD-1 inhibitor and combination therapies in this type of transformed FL.